Problems Of Social Protection of Old Men in New Uzbekistan - Rakhimjon Karimovich Yusupov (Zien Journals, 2021)
The article studies the problems of social gerontology of New Uzbekistan. Various social groups and communities of elderly and old people are being investigated. It was found that the process of demographic aging in Uzbekistan is more typical for women than for men. And also, on the basis of sociodemographic facts, the issues of social protection of the elderly are disclosed. In the conclusion, scientific recommendations for improving the work of the state form of management of social protection of the elderly and old people are presented
Keywords: New Uzbekistan; demographic truth; the process of demographic aging; elderly and old people